TEACHERS’ PERCEPTION OF ONLINE LANGUAGE TEACHING - Debby . Rizky (Universitas Negeri Medan, 2023)
As the ones taking on the responsibility, EFL teachers must master the implementation of online learning, which includes all aspects of the teaching approach, classroom management, and learning media. Based on this phenomenon, this study looked at how English teachers at senior high schools felt about online language teaching. Thus, the findings of this study found two outcomes of online language learning: positive teaching outcomes and negative teaching outcomes. The efficiency of time management and the improvement of technology literacy, which happen for both teachers and students, are included as positive outcomes. Meanwhile, technical issues and classroom management are the main issues contributing to EFL teachers’ negative outcomes. This study suggests further research be conducted on teachers or language instructors from developing countries or with lower socioeconomic backgrounds in the future to examine the effects of intermediate contextual factors on the advantages and obstacles to online teaching and learning in higher education.